DENSITY DEPENDENT PREADULT COMPETITION OF: DROSOPHILA SUBOBSCURA WITH D. SIMULANS AND D. PAVANI (DIPTERA: DROSOPHILIDAE) (Acta Entomológica Chilena, 2022)
Preadult competition for food resources of Drosophila subobscura, D. simulans and D. pavani, underbispecific conditions but with different initial proportions of eggs of each of the species was studied. Theresults showed that in the three species under the competitive conditions used the viability and egg-to-adultdevelopment time varied according to the initial proportion of eggs. D. subobscura was shown to be a badcompetitor with respect to D. simulans and D. pavani.
Keywords: preadult competition, Drosophila subobscura, different proportions of eggs, preadult viability and development time